Challenges of Teacher Prospective Students on the Preparation of Teaching Materials and TPACK-Based Assessment for Micro Teaching Courses - Nuraina, Nuraina; Rohantizani, Rohantizani (SAINTIS Publishing, 2024)
This study examines two main aspects of the challenges faced by prospective teacher students at Malikussaleh University in compiling teaching materials and assessments based on TPACK and TPACK. The background of the problem includes the need for the integration of technology in education which is increasingly important in the digital age. The purpose of this study is to identify these challenges in depth. The method used was qualitative descriptive with data collection through a questionnaire questionnaire distributed to 50 students. The research instrument consists of questions that cover various aspects of challenges in the preparation of teaching materials and assessments. The results of data analysis show that students face significant challenges, especially in mastery of technology and pedagogical integration, with a fairly high percentage of challenges in the preparation of TPACK and TPACK-based assessments. In conclusion, this study emphasizes the need for more attention from educational institutions in providing support to students so that they can overcome these challenges and improve their ability to develop effective and relevant teaching materials and assessments.